TOPSIS Method Implementation for Employee Performance Information System - David Bambang Tri Wijaya; Teguh Wahyono; Aprina Nugrahesthy Sulistya Hapsari (International Journal of Information Technology and Business, 2022)
Employee performance appraisal is one part of human resource activity, to maintain the quality and performance of its employees. Satya Wacana Christian University (SWCU) has also implemented the system, especially for its non-academic employees. The Employee Assessment Process in SWCU has been done by filling out a DP3 form manually, based on the evaluation from the supervisor. The manual assessment process takes a lot of time, because of how many employees need to be evaluated and the lack of objectivity in the assessment. Hence, this research is being done with a purpose to map out and implement a web-based performance assessment information system for the employees, which can then be used to assess those employees’ performance using a computerized system. This research is done to design an information system of performance assessment by applying Technique for Others Reference by Similarity to Ideal Solution (TOPSIS) method so that the assessment process can be done more objectively, quickly, and more importantly easily especially for the multi-criteria assessment process.